1984
DOI: 10.1071/bi9840389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ovarian Hormones on Ovarian Capillary Blood Flow in Anoestrous Ewes

Abstract: The indicator fractionation technique with [86Rb ]rubidium chloride as the indicator was used to determine the relative blood flow (RBF) as a measure of capillary blood flow in the ovaries of conscious, hormonally treated, anoestrous ewes. Treatment of ewes with either progesterone only or oestradiol only had no effect on ovarian RBF, but treatment with oestradiol subsequent to progesterone caused a significant increase (P< 0.(01).Consequently, it appears that progesterone-induced sensitivity of the ovarian va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Unlike the vasculature in other reproductive organs such as the uterus and the oviducts, the ovarian vasculature seems relatively insensitive to peripheral concentrations of oestradiol. This notion is supported not only by the absence of a concurrent increase in capillary blood flow in the contralateral non-ovulatory ovary at ovulation but also by the fact that the mean level of flow in such ovaries (see Table 2 (Brown & Mattner, 1984 …”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Unlike the vasculature in other reproductive organs such as the uterus and the oviducts, the ovarian vasculature seems relatively insensitive to peripheral concentrations of oestradiol. This notion is supported not only by the absence of a concurrent increase in capillary blood flow in the contralateral non-ovulatory ovary at ovulation but also by the fact that the mean level of flow in such ovaries (see Table 2 (Brown & Mattner, 1984 …”
Section: Discussionsupporting
confidence: 48%
“…A study with anoestrous ewes on the effects of ovarian hormones on the ovarian vasculature (Brown & Mattner, 1984) showed that progesterone treatment before oestrogen produced a signifi¬ cant rise in ovarian stromal capillary blood flow while treatment with oestrogen alone or progester¬ one alone had no such effect. This, together with the finding that ovarian stromal blood flow normally increases at oestrus in cyclic ewes (Brown et ai, 1974), suggests that the rate of ovarian blood flow around ovulation may be a critical factor for normal ovarian function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-operative analgesia and antibiotic cover was provided in the form of a non-steroidal anti-inflammatory drug (2.2 mg kg −1 ; Finadyne, Shering Plough Animal Health, Herts, UK) and broad spectrum antibiotic (3–4 ml animal −1 , Streptacare, Animal Care, Ltd, York, UK) for 3–5 days after surgery. Prior to aTP, each ewe was treated with a regime of progesterone and estradiol benzoate previously shown to increase ovarian and uterine blood flow (Brown and Mattner, 1984). This regime consisted of progestagen impregnated sponges (flugestone acetate; Chronogest CR, Intervet UK Ltd, Milton Keynes, UK) implanted intravaginally for 10–11 days, with sponge withdrawal and estradiol benzoate injection (100 µg animal −1 ) on the day before aTP.…”
Section: Methodsmentioning
confidence: 99%
“…The sponges were removed immediately after the cannulation procedure, 36-40 h before blood flow measurement. Pre-treatment of ewes with progesterone only, has no effect on ovarian capillary blood flow (Brown & Mattner, 1984).…”
Section: Methodsmentioning
confidence: 99%